2021
DOI: 10.4209/aaqr.210081
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of Traffic Emissions on Fine Particulate Matter and Carbon Monoxide Levels in Hanoi through COVID-19 Social Distancing Periods

Abstract: Hanoi, Vietnam, is usually ranked as one of the most polluted capital cities in terms of air quality, particularly PM2.5. However, there has not been enough data to determine the main source of this pollution. In this study, we utilized the rare opportunity of the COVID-19 social distancing to assess the contribution of traffic emission to PM2.5 and CO levels when traffic volume was reduced significantly in Hanoi. Hourly PM2.5 and CO concentrations were measured from nine urban and traffic monitoring stations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…The mean percentage of IHD patients increased significantly in Incheon and Gwangju, whereas it decreased in Seoul and Suwon after SD. This decline in patient visits after SD can be attributed to the government’s implementation of quarantine measures to prevent COVID-19 infections, which was more strictly enforced during this period than before SD to further reduce air pollution 19 20 21 22 23 and curb the spread of infectious diseases. 26 The WHO reported that “each suicide in a population is accompanied by more than 20 suicide attempts.” 29 Therefore, we can estimate that the same patients visited EDs several times for treatment after suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean percentage of IHD patients increased significantly in Incheon and Gwangju, whereas it decreased in Seoul and Suwon after SD. This decline in patient visits after SD can be attributed to the government’s implementation of quarantine measures to prevent COVID-19 infections, which was more strictly enforced during this period than before SD to further reduce air pollution 19 20 21 22 23 and curb the spread of infectious diseases. 26 The WHO reported that “each suicide in a population is accompanied by more than 20 suicide attempts.” 29 Therefore, we can estimate that the same patients visited EDs several times for treatment after suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…21 Several studies reported a decrease in PM 2.5 levels as a result of the lockdown and the implementation of SD measures in response to the COVID-19 epidemic. 22 23 24 These measures represented a public health infection control strategy aimed at minimizing individual or group contact to reduce the transmission of infectious diseases. The measures are considered non-pharmaceutical interventions, meaning they do not involve the use of treatments or vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…NO 2 concentrations during the COVID-19 lockdown period decreased slightly by 8.2% over the urban ambient station in the Metro of Atlanta, USA [ 21 ]. PM 2.5 concentrations in Hanoi, Vietnam, were about 14–18% lower during the COVID-19 epoch than before this era, but CO concentrations had a significant decline by about 28–41% [ 22 ]. The control measures during the COVID-19 pandemic reduced NO 2 levels in China [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Countries have taken various actions to control and confront this infectious disease such as: staying at home and keeping social distancing (Şahin, 2020). Furthermore, many regions imposed lockdown and movement restrictions as one of the most effective measures for minimizing the risk of virus contractions (Le et al, 2021). Execution of the lockdown policy not only has had implications for curbing the pandemic but also highly impacted the transportation system worldwide (Ranjbari et al, 2021), and consequently, improvement of the air quality in different parts of the world (Gautam, 2020;Chen et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Aside from the city and regional scale studies which considered the effect of lockdowns on the pollution emitted by the transportation system (Gualtieri et al, 2020;Şahin, 2020;Wang et al, 2020a;Chen et al, 2021;Le et al, 2021), some research has been done at the intra-urban level. Xiang et al (2020) conducted research to examine the impacts of the COVID-19 responses on traffic-related air pollution utilizing flow data collected by the loop sensors for several links in the street network along with the pollution data gathered from a roadside monitoring station.…”
Section: Introductionmentioning
confidence: 99%